Teacher Speech Style and Student Engagement in ELT: A Systematic Review - Nazar Hasby; Maria Arina Luardini; Indra Perdana; Misrita; Pajrian Noor; Lailatul Kodriyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This systematic review investigated the influence of teacher speech style on student engagement in English language learning. It examined various speech elements, including intonation, speaking speed, use of body language, and teacher-student interaction, to explore how these factors impacted students' participation and motivation. By analyzing studies published between 2020 and 2024, the review highlighted that teachers who adapted their speech styles to students' social characteristics and linguistic abilities fostered a more engaging and interactive learning environment. Intonation variations, appropriate speaking speed, the strategic use of humor, and a democratic speaking style were found to have significantly increased student engagement. This research contributed to understanding how speech style could be used as a pedagogical tool to enhance language learning and suggested that teacher training programs should incorporate techniques to refine these aspects of teaching for greater student involvement.